1976
DOI: 10.1159/000152839
|View full text |Cite
|
Sign up to set email alerts
|

Blood Group Genetic Studies in an Urban Chinese Population

Abstract: The distribution of the blood group systems ABO, Rhesus, MNSs and P was studied in all or some of 1,007 Singapore Chinese. ABO gene frequencies were found to be consistent with previous studies and did not vary significantly between dialects. An individual of phenotype A2B was detected although the population showed no other evidence for the A2 gene. The possible significance of this observation in terms of weak H alleles in the population is discussed. The frequencies of the MNSs genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…There was a marked difference in the frequency of q and r in these two groups of Chinese (x21 = 6.44 and 3.10, respectively) and they were respectively 0.15 and 0.28 for q; and 0.69 and 0.55 for r in Fujien and Hopeh provinces. In general, the frequencies of p , q, and r in the studied populations are within the range of allelic frequencies published in Han Chinese in China and overseas (Wiener et al, 1944;Simmons et al, 1950;Sussman, 1956;Hawkins and Simons, 1976;Saha et al, 1975;Mourant et al, 1976). The range ofp in the Chinese in the above studies has been reported to vary from 0.15 to 0.25; that of q from 0.17 to 0.24 and r from 0.54 to 0.67.…”
Section: Abosupporting
confidence: 79%
“…There was a marked difference in the frequency of q and r in these two groups of Chinese (x21 = 6.44 and 3.10, respectively) and they were respectively 0.15 and 0.28 for q; and 0.69 and 0.55 for r in Fujien and Hopeh provinces. In general, the frequencies of p , q, and r in the studied populations are within the range of allelic frequencies published in Han Chinese in China and overseas (Wiener et al, 1944;Simmons et al, 1950;Sussman, 1956;Hawkins and Simons, 1976;Saha et al, 1975;Mourant et al, 1976). The range ofp in the Chinese in the above studies has been reported to vary from 0.15 to 0.25; that of q from 0.17 to 0.24 and r from 0.54 to 0.67.…”
Section: Abosupporting
confidence: 79%
“…Hawkins (23) reviewed the literature on the distribution of blood genetic markers in Chinese populations around the world and found quite substantial differences in ABO blood group frequencies in large studies of Chinese in Singapore compared with Hong Kong and Kuala Lumpur. Believing that this may reflect the heterogeneous origins in China of migrants to the three capitals, Hawkins and Simons (24) later studied the ABO blood group distribution of 1007 Singapore Chinese classified by linguistic dialect group and found no significant differences between speakers of Hokkien, Teochew, and Cantonese.…”
Section: Discussionmentioning
confidence: 99%
“…A common weak A allele in Caucasians is ABO*A201 (1061⌬C; fs384), which is 20 amino acids longer than normal due to a frameshift mutation near the stop codon. The A 2 phenotype is found in 20% of white group A donors but is virtually absent among Asians, who tend to express weak B alleles (2,7).…”
Section: Abo and Lewis Geneticsmentioning
confidence: 99%